The analysis and tendency of development of the market of poultry-farming production in Kazakhstan - Musabekov, K; Yesbolova, A (Journal of Economic Research & Business Administration, 2016)
One of the most effective branches of agro-industrial complex is a poultry farming providing the greatest return of production on unit of the spent material resources. From the economic point of view, a major factor of development of branch of poultry farming is existence of the balanced market.In the conditions of import dependence, improvement of formation of the domestic market of production of poultry farming is one of actual prob-lems of science and practice which decision will allow sating the market with dietary and high-quality food. Providing the population of Kazakhstan with products, in particular production of poultry farming of own produc-tion is a main task. At the same time there are a number of problems: the raised costs for production fowl and eggs, backwardness of infrastructure of a sales market, transport remoteness of settlements from sales markets.